CONSTRUCTION AND TECHNOLOGICAL ANALYSIS OF THE BROACH BLADE SHAPE USING THE FINITE ELEMENT METHOD - BŁAWUCKI, Stanisław; ZALESKI, Kazimierz (Applied Computer Science, 2017)
The paper presents results of numerical FEM analyses of the process of broaching the groove using the Explicit module of the ABAQUS program. The impact of the blade geometry was presented and of the selected technological parameters of processing when cutting the aluminium EN-AW 6061-T6 alloy on the load of the broach blade during its operation. This article shows influence of value of rake and clearance angle onto deformations of the tool’s cutting edge in the transverse direction. An interaction between broach blade shape and reduced stress in the area of cutting edge was presented. The optimum geometry of the cutting tool was proposed.